أديسيوس العربي: التأويل وتجربة المترجم وهويته - شيخ الشباب عمر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The hermeneutic approach was developed by German scholars (Lafont 1999) mainly within philosophy. The present paper elaborates on a theoretical linguistic designate named the Interpretive Frame (IF) (Al-Shabab 2007). It investigates two elements of the IF, experience and identity, showing how the translator uses his own experience to project his identity in his translation. The experience of the translator of Tennyson’s “Ulysses” finds its echoes in the wandering and suffering of Ulysses. Arabic language and culture, which have a tendency to favour lyrical poetry and heroic characters, provide the translator with a rich background enabling him to creatively express his identity. Thus, the translated poem portrays the translator as a determined traveller looking in the horizon for further experience and far away lands. تطور المنهج التأويلي على يد الباحثين الألمان (انظر لافونت 1999) في أحضان الفلسفة. ويعتمد البحث الحالي منظومة نظرية لغوية تعرف بالإطار التأويلي اقترحها (الشباب 2007). ويستقصي البحث عنصرين من عناصر الإطار التأويلي هما: التجربة والهوية، مبيناً كيف يستعمل المترجم تجربته الخاصة مغترباً ليعبر عن هويته في ترجمته. وتجد تجربة المترجم في قصيدة ((أديسيوس)) للشاعر الانكليزي تنيسون صداها في التجوال والألم عند أديسيوس. ومن المعروف أن اللغة العربية والثقافة العربية تميلان إلى الغنائية في الشعر وإلى رسم الشخصيات البطولية، مما يعطي المترجم/الشاعر في هذه الترجمة خلفية غنية تمكنه من التعبير عن هويته بشكل إبداعي. هكذا تصور القصيدة المترجمة المترجم كمسافر تزيده السنون تصميماً على المضي في البحث بالأفق عن تجارب جديدة وبلاد بعيدة.